2023
DOI: 10.1200/go.22.00259
|View full text |Cite
|
Sign up to set email alerts
|

Human Papillomavirus–Associated Head and Neck Malignancies in Sub-Saharan Africa: A Systematic Review

Abstract: PURPOSE The proportion of head and neck cancers (HNCs) with human papillomavirus (HPV) positivity in sub-Saharan Africa (SSA) is poorly characterized. Characterizing this has implications in staging, prognosis, resource allocation, and vaccination policies. This study aims to determine the proportion of HPV-associated HNC in SSA. MATERIALS AND METHODS This systematic review included searches from PubMed, EMBASE, Web of Science, African Index Medicus, Google Scholar, and African Journals Online. All English pub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 59 publications
1
3
0
Order By: Relevance
“…From our HPV L1 sequences analysis, HPV18 emerged as the HPV type in the two cancers. This is consistent with literature as HPV16 and 18 have been reported as the most common HPV types in cancers [28][29][30][31][32]. Though HPV16 is mostly reported as the predominant HPV type of the two, a study by Donkoh et al in Kumasi, a city in Ghana, did not detect HPV16 as the most prevalent HPV type while HPV18 was reported as the fourth most common genotype after HPV 52, 56, and 35 among women who had never experienced cervical screening [29].…”
Section: Discussionsupporting
confidence: 88%
“…From our HPV L1 sequences analysis, HPV18 emerged as the HPV type in the two cancers. This is consistent with literature as HPV16 and 18 have been reported as the most common HPV types in cancers [28][29][30][31][32]. Though HPV16 is mostly reported as the predominant HPV type of the two, a study by Donkoh et al in Kumasi, a city in Ghana, did not detect HPV16 as the most prevalent HPV type while HPV18 was reported as the fourth most common genotype after HPV 52, 56, and 35 among women who had never experienced cervical screening [29].…”
Section: Discussionsupporting
confidence: 88%
“…Of note, these ASIR estimates reported by Lu et al extrapolated the AF of 58.5% from one study in South Africa for the region [ 4 ]. A recent systematic review in Sub-Saharan Africa reported that the p16 positivity among oropharyngeal cases was 20.3%, while the HPV PCR positivity was 15.1% among 31 studies representing 12 countries [ 26 ]. Future studies are needed to establish more accurate regional estimates.…”
Section: Global Epidemiology and Regional Variations Of Human Papillo...mentioning
confidence: 99%
“…Given the resource limitations for testing of HPV association, it is unclear whether the latest AJCC/UICC staging system is appropriate for resource-constrained health systems which cannot routinely perform testing [ 38 ]. Variations in and lack of testing capacity influence the availability of epidemiologic data which can then further influence investment in HPV testing infrastructure and vaccination policies [ 26 ].…”
Section: Global Epidemiology and Regional Variations Of Human Papillo...mentioning
confidence: 99%
“… 19 Surveillance for malignancies may also be lower among PWH as compared to the general population, and human papilloma virus (HPV) infection together with snuff use may put PWH at higher risk of nasopharyngeal cancer. 20 Importantly, few tobacco cessation strategies have been developed and tested for PWH, especially in low-resourced settings. PWH are also less likely to quit tobacco use as compared to people without HIV.…”
Section: Introductionmentioning
confidence: 99%